A Study on Indigenous Technical Knowledge of Tribal Farmers in Agriculture and Livestock Sectors of Koraput District - Lenka, Sasanka; Satpathy, Abhijeet (Indian Journal of Extension Education, 2020)
Indian people are living in varied agro-climatic situations with rich cultural values in diversified societies. Several experiments are being taken by the tribal farmers since long on trial and error basis on agriculture and allied activities to overcome the specific problems or adverse situations in their respective areas. Indigenous technical knowledge system consists of an integrated body of knowledge system which tends to focus on different aspects of agricultural sciences i.e. agriculture, animal husbandry, and natural resource management. The paper is focused on the documentation of various Indigenous Technical Knowledge (ITK) of tribal farmers in agriculture and animal husbandry sectors. Odisha is a state populated by several indigenous communities, most of which have their own set of unique traditional knowledge and technology base. The majority of the tribal farmers had a favorable attitude towards Indigenous Technical Knowledge in the agriculture and livestock sectors. It is a key element of the social capital of the poor and constitutes their asset in their efforts to gain control of their own lives. The flow of indigenous knowledge communication is necessary for the preservation, development, and sustainability of local wisdom. It can be concluded that about 56 per cent of agricultural ITKs are rational against 44 per cent are non-rational. Similarly, 62 per cent of ITKs found in the livestock sector are rational against 38 per cent are non-rational. The rate of adoption in livestock ITKs was 75 per cent and for agriculture 65.72 per cent showing significantly higher rate of adoption in livestock than agriculture. Mainly the farmer’s traditional knowledge is vital for all the well-being categories for sustainable development as it has evolved after thousands of years of observation and experience. ITKs being low in cost, it will also benefit the national economy besides sustainable agricultural development.
Keywords: Agricultural extension; Indigenous Technical Knowledge (ITK); Documentation and validation